2022
DOI: 10.1590/fst.17822
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, preparation, and carboxymethyl of polysaccharide from Lotus root

Abstract: In this study, we extracted lotus root polysaccharide (LRP) and synthesized carboxymethylated lotus root polysaccharide (CM-LRP) using response surface methodology (RSM). The monosaccharide component of LRP was analyzed by pre-column derivatization high performance liquid chromatography (PCD-HPLC). The polysaccharide was characterized by ultraviolet (UV) spectroscopy scan, Fourier transform infrared spectroscopy (FTIR), circular dichroism spectrometer (CD), and scanning electron microscopy (SEM). It was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…This traditional method uses hot water as a solvent to boil certain plant parts for hours, usually followed by lyophilization, purification, and adding ethanol or methanol in a few studies for precipitation of crude polysaccharides [ 1 , 4 , 10 , 11 , 14 , 22 , 45 , 57 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 ]. The phenol sulfuric acid method is then used to measure the content of acquired polysaccharides [ 90 , 92 , 95 , 96 , 97 , 98 ]. After ethanol precipitation, products mainly contain polysaccharides, whereas the ones lyophilized without precipitation contain other constituents, such as polyphenols [ 4 , 24 , 47 , 87 ].…”
Section: Extraction Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This traditional method uses hot water as a solvent to boil certain plant parts for hours, usually followed by lyophilization, purification, and adding ethanol or methanol in a few studies for precipitation of crude polysaccharides [ 1 , 4 , 10 , 11 , 14 , 22 , 45 , 57 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 ]. The phenol sulfuric acid method is then used to measure the content of acquired polysaccharides [ 90 , 92 , 95 , 96 , 97 , 98 ]. After ethanol precipitation, products mainly contain polysaccharides, whereas the ones lyophilized without precipitation contain other constituents, such as polyphenols [ 4 , 24 , 47 , 87 ].…”
Section: Extraction Methodsmentioning
confidence: 99%
“…Many diseases are related to free radicals and ROS, such as aging, heart diseases, or diabetes mellitus [ 162 , 164 , 165 ]. The abilities to scavenge free radicals are typically observed and analyzed in vitro by using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and ABTS, creating fade at 517 nm and 734 nm, respectively, with vitamin C (Vc) or butylated hydroxytoluene (BHT) as the positive controls [ 5 , 9 , 25 , 37 , 46 , 96 , 166 ]. The color fade can then be observed through spectrophotometry to analyze the radical scavenging abilities of a bioactive component [ 25 , 37 , 46 ].…”
Section: Medical Properties Of the Sanghuang Speciesmentioning
confidence: 99%
“…The FT-IR spectra of zein and Z-SP were obtained on a Nico-let FT-IR 20 SX spectrometer (Nicolet, USA) based on the KBr method (Yan et al, 2022;Forato et al, 2003). The measurements were carried at 4 cm -1 resolution with 32 scans in the mid-infrared region (4000-400 cm -1 ).…”
Section: Fourier Transform Infrared (Ft-ir) Spectroscopymentioning
confidence: 99%
“…Studies have shown that the lotus leaf alkaloid is insoluble in water, although it can be absorbed and involved in metabolism under the condition of lipid solubility in the body, but the onset of action is slow and cannot be fully utilized. Another study found that the alkaloid salts have good water solubility, the alkaloid in the lotus leaf are extracted in the form of salt, which is not only conducive to optimizing the resources, improving the utilization rate and the economic benefits, but also facilitates better absorption by the body (Yan et al, 2022b). Therefore, it has important academic value and application prospect to study the optimization of extraction process conditions of lotus leaf alkaloids.…”
Section: Introductionmentioning
confidence: 99%